(untitled) (La U Investiga, 2023)
Eating habits (HA), perception of body image (PIC) and emotional state are key aspects to consider during youth, university students could suffer alterations in these sections. The objective of this study was to determine the eating habits, perception of body image and emotional state in students of the Universidad Técnica del Norte (UTN) in the period from May to July 2022. It was a cross-sectional quantitative descriptive study in 104 university students. of undergraduate of the faculties of the UTN. HA was measured through the Adolescent Food Habits Checklist (AFHC), ICP through the Body Shape Questionnaire (BSQ) and emotional state through an emotional stability scale that allowed it to be classified as low, normal or high. 67.31% were female, the age was 22.45±2.27 years, 75% were mestizos and almost all were single (95.19%). Regarding the HA, 81.73% were healthy, on the other hand, similar percentages of satisfaction and mild body dissatisfaction were found (55.77% and 44.23% respectively). Additionally, 90.38% had a good emotional state. No statistically significant association was found between the level of body satisfaction and emotional state in relation to HA in university students (p ˃0.05). It was concluded that almost all university students have healthy eating habits and a good emotional state, however, more than half of them have mild body dissatisfaction, despite this the association between these variables is not significant.